12th annual CVMBS research day scientific proceedings - Colorado State University. College of Veterinary Medicine and Biomedical Sciences, author (Colorado State University. Libraries, 2011)
Includes the Pfizer Research Award winner and abstracts only of the oral sessions and posters.
CVMBS research day 2011
Colorado State University, College of Veterinary Medicine and Biomedical Sciences, 12th annual CVMBS research day scientific proceedings
Held in the Hilton Hotel on March 5, 2011, Fort Collins, Colorado.
Keywords: Veterinary medicine -- Congresses; Veterinary medicine -- Research -- Congresses